Nosocomial outbreak of cryptosporidiosis in AIDS patients. Issue 6771 (2nd February 1991) - Ravn, P; Lundgren, J D; Kjaeldgaard, P; Holten-Anderson, W; Højlyng, N; Nielsen, J O; Gaub, J
Abstract : OBJECTIVE--To describe a nosocomial outbreak of cryptosporidiosis during four months after June 1989. SETTING--A department of infectious diseases in Copenhagen, seeing about half the patients with AIDS in Denmark. SUBJECTS--73 HIV antibody negative subjects and 60 antibody positive subjects admitted as inpatients during the transmission period of the outbreak (20 June-14 August), of whom 18 (17 with AIDS, one with AIDS related complex), developed cryptosporidiosis. Two further HIV negative subjects (one departmental secretary, one visiting relative) developed cryptosporidiosis. MAIN OUTCOME MEASURES--Cryptosporidia in stool samples, clinical symptoms, CD4 cell count, HIV antigen concentration, chemotherapeutic treatment. RESULTS--The source of the outbreak was identified as ice from an ice machine in the ward, contaminated by an incontinent, psychotic patient with cryptosporidiosis picking out ice for cold drinks. The mean incubation time was at least 13 days-that is, twice that in HIV-negative patients. Of the 18 patients with AIDS who developed cryptosporidiosis, five recovered, two were symptomless carriers, three died of unrelated causes, and eight died after prolonged diarrhoea. Among the 57 exposed HIV antibody positive inpatients (excluding two patients and the index case with cryptosporidiosis diagnosed elsewhere), significantly more of those who developed symptomatic cryptosporidiosis received oral sulphonamides than those who did not (91%, 10/11 v 48%, 21/44, p less than 0.05). CONCLUSIONS--The clinical and epidemiological findings indicate that infection was the consequence of very small inocula. Increased sensitivity to cryptosporidiosis may be an unrecognised side effect of oral sulphonamide treatment in patients with AIDS.